Rapeseed oil spray development of diesel idi spray nozzle under air movement influence - Sapit, Azwan; Mohammed, Akmal Nizam; Razali, Mohd. Azahari; Hushim, Mohd Faisal Bin; Khalid, Amir; Manshoor, Bukhari (Asian Research Publishing Network (ARPN), 2016)
Rapeseed oil (RO) spray has very slow atomization due to its high viscosity nature. Although high injection pressure, high ambient temperature and combination of nozzle can promote faster atomization of rapeseed oil spray, another factor that was not discussed is the effect air movement that could positively influence RO spray development. To study the effect of air movement, in particular to generate the swirl (air movement inside the chamber), a swirler was used. Images were captured using a nano-spark shadowgraph photography technique and also high speed video imaging. Macrostructures of diesel sprays such as spray tip penetration length, spray shape, spraycone angle were obtained. Microstructures, such as droplet distribution and size were also studied. Result shows that IDI nozzle rapeseed oil spray has a narrow spray cone angle. The average droplet size is around 20~25µm. The large size of rapeseed oil droplet require assistant to improve atomization and results shows rapid air movement in chamber successfully improve atomization